Factors Influencing the Use of Smart Farming Applications by Farmers in Thailand - Mahapittayaphaisan, Mintita; Sasithanakornkaew, Saranthorn; Apisuphachok, Warapan (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aimed to study (1) compare differences between demographic characteristics and smart farming application usage behavior, (2) examine the relationships between perceived usefulness, perceived ease of use, perceived risk, reference groups, and smart farming application usage behavior, and (3) investigate the influence of perceived usefulness, perceived ease of use, perceived risk, and reference groups on smart farming application usage behavior. This study employed a quantitative research approach. The sample consisted of 400 farmers with experience using smart farming applications, selected through non-probability convenience sampling. Data were collected using a structured questionnaire and analyzed using descriptive and inferential statistics. The results indicated that farmers demonstrated high levels of perceived usefulness, perceived ease of use, and smart farming application usage behavior, while perceived risk was at a moderate level. The results of the demographic difference tests showed that gender, age, education level, income and farming experience did not significantly differ in terms of smart farming application usage behavior. Additionally, perceived usefulness (r = 0.180), perceived ease of use (r = 0.352), perceived risk (r = 0.245), and reference groups (r = 0.192) were significantly correlated with smart farming application usage behavior. Multiple regression analysis revealed that perceived ease of use (β = 0.859) and reference groups (β = -0.698) significantly influenced smart farming application usage behavior.